Bird Species Composition, Abundance, Diversity, and Evenness at Panaad Park and Stadium and Provincial Capitol Park and Lagoon, Bacolod City, Negros Occidental - Mabugat, Lance Querubin A.; Catalan, Anton Van J C.; Te, Lara Lois D.; Collarin, Karl Josh L.; Masiado, John Dave R.; Dogelio, Wyeth G.; De Oca, Phillip Raymund R.; Jakosalem, Philip Godfrey C.; Paguntalan, Lisa Marie J. (Silliman Journal, 2024)
This study assessed bird species composition, abundance, diversity, evenness, and species dominance in Bacolod Panaad Park and Stadium and Provincial Capitol Park and Lagoon. The point transect method was employed for seven (7) stations plotted in both locales. Five hundred eleven (511) bird individuals were recorded comprising thirty (30) species. Six (6) were endemic, 19 were residents, 3 were introduced, and 2 were migrants. Only one recorded species, Lonchura oryzivora, which is an introduced species in the Philippines and native to Indonesia, was considered endangered based on the IUCN classification. Meanwhile, Passer montanus was the most abundant in both sites. The assessment also revealed that Panaad Park and Stadium had a higher diversity index and dominance of species, while Provincial Capitol Park and Lagoon had a highly even distribution of the composition of species. Based on habitat assessment, Bacolod Panaad Park and Stadium had a better index of distance to the nearest road, number of trees, and tree height compared to Provincial Capitol Park and Lagoon which was closer to water. Moreover, the results of this study will be used as baseline information in strengthening the urban management in Negros Occidental, with an emphasis on bird diversity.